Impact of ELKa, the Electronic Device for Prandial Insulin Dose Calculation, on Metabolic Control in Children and Adolescents with Type 1 Diabetes Mellitus: A Randomized Controlled Trial - Agnieszka Kowalska; Katarzyna Piechowiak; Anna Ramotowska; Agnieszka Szypowska (Journal of Diabetes Research)
Background. The ELKa system is composed of computer software, with a database of nutrients, and a dedicated USB kitchen scale. It was designed to automatize the everyday calculations of food exchanges and prandial insulin doses. Aim. To investigate the influence of the ELKa on metabolic control in children with type 1 diabetes mellitus (T1DM). Methods. A randomized, parallel, open-label clinical trial involved 106 patients aged <18 years with T1DM, HbA1C≤10%, undergoing intensive insulin therapy, allocated to the intervention group, who used the ELKa (n=53), or the control group (n=53), who used conventional calculation methods. Results. After the 26-week follow-up, the intention-to-treat analysis showed no differences to all endpoints. In per protocol analysis, 22/53 (41.5%) patients reporting ELKa usage for >50% of meals achieved lower HbA1C levels (P=0.002), lower basal insulin amounts (P=0.049), and lower intrasubject standard deviation of blood glucose levels (P=0.023) in comparison with the control. Moreover, in the intervention group, significant reduction of HbA1C level, by 0.55% point (P=0.002), was noted. No intergroup differences were found in the hypoglycemic episodes, BMI-SDS, bolus insulin dosage, and total daily insulin dosage. Conclusions. The ELKa system improves metabolic control in children with T1DM under regular usage. The trial is registered at ClinicalTrials.gov, number NCT02194517.